Inovasi Pelayanan Perizinan dan Akreditasi Lembaga Pendidikan di Dinas Pendidikan dan Kebudayaan Kabupaten Sidoarjo - Nasichuddin Nasichuddin; Sapto Pramono; Sri Roekminiati (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This research focuses on examining the innovation of licensing and accreditation services for educational institutions within the Department of Education and Culture of Sidoarjo Regency, as a strategy to ensure effective, transparent, and accountable education governance in the digital age. This research is based on bureaucratic intricacies, poor integration of information systems, and inadequate digital skills among civil servants in overseeing public education services. This research utilized a qualitative descriptive method, gathering data via in-depth interviews, observations, and documentation involving department personnel, school leaders, and representatives from educational institutions benefiting from the services. The results indicate that service innovation via the deployment of digital systems like the Sidoarjo Education Online System and e-Accreditation has effectively expedited licensing procedures, enhanced administrative efficiency, and bolstered transparency and public information release. Nonetheless, the primary obstacles persist in coordination between departments, opposition to changes in organizational culture, and insufficient human resource skills in managing digital systems. This research highlights that the effectiveness of public service innovation in education relies not just on adopting technology but also on improving collaborative governance and increasing bureaucratic capabilities. The research suggests creating a cooperative, data-informed, and participatory innovation framework to guarantee the sustainability and inclusivity of educational service innovation in Sidoarjo Regency.